Pengaruh Pertumbuhan Uang Beredar terhadap Tingkat Inflasi di Sumatera Utara - Breti Br Karo Sekali; Cristina Martalia Sitepu; Eka Dwina Sitanggang; Pandapotan Tampubolon (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Price stability is a primary prerequisite for sustainable regional economic growth, yet the challenges of money supply fluctuations often trigger inflation dynamics in North Sumatra Province. This study aims to empirically analyze the effect of money supply (M2) growth on the inflation rate in North Sumatra. This research employs a quantitative approach with an analytical descriptive design. The research population encompasses the overall monetary and inflation data of North Sumatra, with a purposively drawn sample of monthly time-series secondary data covering the 2023–2026 period. Data were sourced from official reports by Bank Indonesia and the Central Bureau of Statistics (BPS), collected through documentation study techniques. Data analysis was conducted utilizing a simple linear regression model (Ordinary Least Square) via R Studio software, preceded by comprehensive classical assumption testing. The analysis results indicate that money supply growth has a positive and statistically significant effect (at = 10%) on the inflation rate in North Sumatra, as indicated by a regression coefficient of 0.2258. This implies that every 1% increase in M2 drives a 0.22% rise in inflation, with this monetary variable capable of explaining 7.5% of regional inflation variations. In conclusion, monetary policy through M2 control remains a vital instrument in regional macroeconomic governance. Consequently, it is recommended that monetary authorities strengthen coordination with local governments to maintain optimal market liquidity levels without compromising public purchasing power.